Dampak Pembelajaran Penjas Yang Dimodifikasi Dengan Permainan Bolavoli Terhadap Motivasi Belajar Dan Keterampilan Gerak Dasar Siswa - Hikmad Hakim; Sahabuddin; Muhammad Ishak (PT Mediatama Zayna Indonesia, 2025)
This study aims to examine the impact of Physical Education learning modified with volleyball games on learning motivation and basic movement skills of class VIII students of SMP Negeri 13 Makassar. The method used is quantitative research with a quasi-experimental design, using Non-equivalent Control Group Design. The research sample consisted of 40 students divided into two groups, namely the experimental group that followed modified volleyball game learning and the control group that followed conventional learning. Data were collected through basic movement skills test instruments and learning motivation questionnaires. The results showed an increase in learning motivation in the experimental group from an average of 70.1 (pre-test) to 85.3 (post-test), while the control group only increased from 69.8 to 73.5. Basic movement skills also increased significantly in the experimental group, from 72.4 to 88.7, compared to the control group which only increased from 71.9 to 75.2. The paired t-test and independent t-test proved that the difference in learning motivation and basic movement skills between the two groups was significant at a significance level of 0.05. In conclusion, Physical Education learning modified with volleyball game is effective in increasing students’ learning motivation and basic movement skills. This learning model can be an innovative alternative in improving the quality of Physical Education learning in junior high schools